LING, Roger, Roman Painting. Cambridge: Cambridge University Press, 1991. - Funari, Pedro Paulo Abreu (Classica - Revista Brasileira de Estudos Clássicos, 1993)
LING, Roger, Roman Painting. Cambridge: Cambridge University Press, 1991.